2014
DOI: 10.1167/14.12.4
|View full text |Cite
|
Sign up to set email alerts
|

Emotional content of an image attracts attention more than visually salient features in various signal-to-noise ratio conditions

Abstract: Emotional images are processed in a prioritized manner, attracting attention almost immediately. In the present study we used eye tracking to reveal what type of features within neutral, positive, and negative images attract early visual attention: semantics, visual saliency, or their interaction. Semantic regions of interest were selected by observers, while visual saliency was determined using the Graph-Based Visual Saliency model. Images were transformed by adding pink noise in several proportions to be pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 96 publications
7
38
0
Order By: Relevance
“…The other 53 students (mean age = 19 years, 34 females, 32 Caucasians) participated in experiment 2 to test the effect of color. The sample size was comparable with that of similar previous studies (e.g., De Cesarei and Codispoti, 2008 ; Nummenmaa et al, 2010 ; Pilarczyk and Kuniecki, 2014 ). The participants for both experiments were representative in the same manner of the psychology major undergraduate population at Dartmouth College with respects to age, gender and ethnicity.…”
Section: Methodssupporting
confidence: 79%
“…The other 53 students (mean age = 19 years, 34 females, 32 Caucasians) participated in experiment 2 to test the effect of color. The sample size was comparable with that of similar previous studies (e.g., De Cesarei and Codispoti, 2008 ; Nummenmaa et al, 2010 ; Pilarczyk and Kuniecki, 2014 ). The participants for both experiments were representative in the same manner of the psychology major undergraduate population at Dartmouth College with respects to age, gender and ethnicity.…”
Section: Methodssupporting
confidence: 79%
“…Emotional stimuli may influence prospective memory through encoding or retrieval processes, or synergistically through both. The findings from the more general literature of emotion and cognition suggests that emotion is likely to improve the encoding process through enhanced attention and visual processing (Calvo & Lang, 2004;Dolan, 2002;Nummenmaa, Hyona, & Calvo, 2006;Phelps, Ling, & Carrasco, 2006;Pilarczyk & Kuniecki, 2014). Emotion can also enhance the memory consolidation of stimuli (Mather, 2007) by acitvating the amygdala (Hamann, 2001) and resulting in enhanced long-term (Hamann, Ely, Grafton, & Kilts, 1999) and short-term memory (Hamann & Mao, 2001, cited in Hamann, 2001).…”
Section: The Influence Of Emotion On Cognitionmentioning
confidence: 99%
“…Relatedly, eye-movement studies have revealed (a) greater attentional capture by emotional relative to neutral scenes, when they are presented alone (Kissler & Keil, 2008) or simultaneously (Alpers, 2008;McSorley & van Reekum, 2013;Nummenmaa, Hyönä, & Calvo, 2006 in extrafoveal vision; and (b) selective orienting to extrafoveal scene areas depicting emotional objects relative to non-emotional objects within the same scene (Humphrey, Underwood, & Lambert, 2012;Niu, Todd, & Anderson, 2012;Pilarczyk & Kuniecki, 2014).…”
Section: Introductionmentioning
confidence: 99%